Application of the compressed sensing technique to self‐gated cardiac cine sequences in small animals. Issue 2 (16th September 2013) - Montesinos, Paula; Abascal, Juan Felipe P.J.; Cussó, Lorena; Vaquero, Juan José; Desco, Manuel
<x xml:space="preserve">Abstract</x> Purpose Self‐gated cine sequences are a common choice for cardiac MRI in preclinical applications. The aims of our work were to apply the compressed sensing technique to IntraGateFLASH cardiac MRI studies on rats and to find the maximum acceleration factor achievable with this technique. Theory and Methods Our reconstruction method extended the Split Bregman formulation to minimize the total variation in both space and time. In addition, we analyzed the influence of the undersampling pattern on the acceleration factor achievable. Results Our results show that acceleration factors of up to 15 are achievable with our technique when appropriate undersampling patterns are used. The introduction of a time‐varying random sampling clearly improved the efficiency of the undersampling schemes. In terms of computational efficiency, the proposed reconstruction method has been shown to be competitive as compared with the fastest methods found in the literature. Conclusion We successfully applied our compressed sensing technique to self‐gated cardiac cine acquisition in small animals, obtaining an acceleration factor of up to 15 with almost unnoticeable image degradation. Magn Reson Med 72:369–380, 2014. © 2013 Wiley Periodicals, Inc.